Odpowiedź:
Szczegółowe wyjaśnienie:
zadanie 1
a) 3(5x+4) -6(2-x) = 15x+12-12+6x = 21x
b) -2(4x-3) -3(4-2x) = -8x+6-12+6x = -2x-6
c) 3p²+ 12p / 3p = p+4
d) (10x-6/2) - 10-35x/5 = 5x-3 -2-6x = -x -5
e)-(3x-2) - (-4x+6) - (8x+5) = -3x+2+4x-6-8x-5 = -7x-9
f) (-15a-20b+5) : (-5) = 3a+4b-1
zadanie 2
a) -3(4+2a) -2(5a-4)+(-6a-8) = -12-6a -10a+8-6a-8= -12 -22a
-12 -22a = -12 -22 · (1/2) = -12 -11= - 23
b) -(3x-2)(-4+x)= (-3x+2)(-4+x) = 12x-3x² -8+2x= 14x -3x²-8
14x-3x²-8= 14·2 -3·2²-8= 28-3·4-8=28-12-8= 8
c) 9(-x+2y) -4(-y+2x) = -9x+18y+4y-8x = -17x +22y
-17x+22y = -17·(-5/34)+ 22·(-10/11) = 5/2 + (-20) = 5/2 - 40/2 = -35/2 = -17 1/2